Development of integrated science instructional materials using Rowntree model to promote 21st century ecoliteracy - Azmi Al Bahij; Julia Anis Handayani; Apri Utami Parta Santi; Erna Yayuk (Research and Development in Education (RaDEn), 2025)
The 4.0 Revolution and 21st-century challenges necessitate an education system that integrates 4C skills (Critical Thinking, Communication, Collaboration, and Creativity) with environmental awareness. This study aims to develop and evaluate the feasibility, practicality, and effectiveness of Integrated Science learning tools focused on ecoliteracy for fourth-grade elementary school students. Using the Research and Development (RnD) method with the Rowntree model, the development process progressed through three stages: planning, development, and evaluation. The research was conducted at FIP UMJ Lab School with 19 students and one teacher as subjects. Data were collected using validation sheets, questionnaires, and pre-test/post-test instruments. The results demonstrate high validity across all aspects: language (98%), media (94%), and material (88%), categorizing the tools as "highly valid." Practicality tests yielded excellent scores from the teacher (96.7%) and students (94.7%), indicating that the tools are user-friendly and engaging. Furthermore, the effectiveness test showed an N-Gain score of 0.478 (medium category), proving that the tools significantly improve student learning outcomes. In conclusion, the Rowntree-based integrated science learning tools are feasible and effective for fostering ecoliteracy and 21st-century skills in primary education, providing a holistic solution to environmental education challenges.